2010
DOI: 10.1371/journal.pone.0013616
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Status in Humans and Content of Phosphorylated Thiamine Derivatives in Biopsies and Cultured Cells

Abstract: BackgroundThiamine (vitamin B1) is an essential molecule for all life forms because thiamine diphosphate (ThDP) is an indispensable cofactor for oxidative energy metabolism. The less abundant thiamine monophosphate (ThMP), thiamine triphosphate (ThTP) and adenosine thiamine triphosphate (AThTP), present in many organisms, may have still unidentified physiological functions. Diseases linked to thiamine deficiency (polyneuritis, Wernicke-Korsakoff syndrome) remain frequent among alcohol abusers and other risk po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
157
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(179 citation statements)
references
References 97 publications
11
157
0
3
Order By: Relevance
“…Free thiamine could then move out of the cell across the basolateral membrane via the previously characterized THTR-1, which is expressed in colonocytes (12). As for TMP, this thiamine metabolite does exist in considerable amounts in the plasma (30), and, thus, it is possible that it can also leave the colonocyte via a yet to be identified transport system. Whether TPP itself can also cross the colonic basolateral membrane (knowing that there is some TPP in the plasma (31)) is not clear and requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Free thiamine could then move out of the cell across the basolateral membrane via the previously characterized THTR-1, which is expressed in colonocytes (12). As for TMP, this thiamine metabolite does exist in considerable amounts in the plasma (30), and, thus, it is possible that it can also leave the colonocyte via a yet to be identified transport system. Whether TPP itself can also cross the colonic basolateral membrane (knowing that there is some TPP in the plasma (31)) is not clear and requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This 25-kDa cytoplasmic protein is a highly efficient ThTPase ubiquitously expressed in adult mammalian tissues. However, it seems to be most 5 abundant in highly differentiated cells while it is hardly detectable in cultured cells, suggesting that the expression of this enzyme is linked to the degree of cellular differentiation 20,21 .…”
Section: The Case Of Thiamine Triphosphatementioning
confidence: 99%
“…However, in those organisms where 25-kDa ThTPase is absent (chicken) or catalytically inefficient (fish, pig), cytosolic ThTP indeed accumulates and, in skeletal muscles and electric organs its levels can even exceed those of ThDP, but without apparent toxic effect 21 . It is possible that ThTP has mainly a mitochondrial role, i. e., intramitochondrial ThTP synthesized by F o F 1 -ATP synthase is the physiologically relevant pool, while cytosolic ThTP synthesized by adenylate kinase would be only a by-product of this enzyme activity.…”
Section: The Case Of Thiamine Triphosphatementioning
confidence: 99%
“…Apparently, in both forms (type 1 and type 2) of diabetic condition there is about 70 % thiamine deficiency as measured in the plasma of diabetic patients [13][14][15] but the physiological mechanism associated with this deficiency has not been clarified yet. However, a number of studies found an altered thiamine handling in the kidneys of diabetic patients [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies found an altered thiamine handling in the kidneys of diabetic patients [16][17][18]. Benfotiamine, (S-benzoylthiamine-Omonophosphate), a derivative of the vitamin B1 or thiamine, has a much higher bioavailability than thiamine and, as a result, accumulates in the target tissues much more than thiamine itself [15,19,20]. Thiamine absorption from oral benfotiamine is approximately five times greater than from conventional thiamine supplements [21][22][23].…”
Section: Introductionmentioning
confidence: 99%